Marriage and Pre-Nuptial Agreements – between Impediment and Responsible Acceptance of the Fruits of Marriage: a Legal-Historical Experience between the 15th and 20th Centuries - Holcman, Borut (65 pravne znanosti v Mariboru, 2026)
Matrimony is a union that spans both spiritual-intimate and material dimensions. Both dimensions are significant. The significance of these dimensions reflects in the ethical-religious, Christian-Catholic, and political-social understanding of matrimony, as well as in the formalities entrusted to notaries. It follows that, in the case of marital union, the history of civil law cannot be separated from the history of canon law, nor from their manifestations up to the present day. The good of the marital union (maritalis affectio) is thus part of both dimensions, civil law and canon law. The historical-legal doctrine of the property law regulation of marital relations, presented in the consensus sponsalitius (prenuptial agreement), serves as the foundation for future life as partners and the potential resolution of conflict situations. Sponsalia de futuro or sponsalia de praesenti, viewed from a historical-legal perspective and taking into account the normative regulation of matrimonial law from both civil and canon law standpoints, offer a different perspective on the responsibilities of future spouses. Despite the contradiction posed primarily by the ethical-religious dimension, legal history offers sufficient practical starting points.